1995
DOI: 10.1001/archinte.1995.00430210080012
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Low-Density Lipoprotein Cholesterol Levels in an Ambulatory Care System

Abstract: These results support multidisciplinary, goal-oriented collaborative practice as an efficacious model of preventive medicine and health care provision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…One effective model tested in clinical trials of hypertension, diabetes mellitus, congestive heart failure, cigarette cessation, and hyperlipidemia, is the use of non-physician health care providers guided by treatment algorithms and physician supervision (Haskell et al, 1994;Lasater, 1996;Mundinger et al, 2000;Schectman et al, 1996;Schultz & Sheps, 1994;Shaffer & Wexler, 1995;Taylor et al, 1990;Weinberger et al, 1995). The current study was an attempt to apply the results of such trials to a 'real world' setting in order to evaluate its costs, applicability, acceptability (to both patients and physicians) and clinical effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…One effective model tested in clinical trials of hypertension, diabetes mellitus, congestive heart failure, cigarette cessation, and hyperlipidemia, is the use of non-physician health care providers guided by treatment algorithms and physician supervision (Haskell et al, 1994;Lasater, 1996;Mundinger et al, 2000;Schectman et al, 1996;Schultz & Sheps, 1994;Shaffer & Wexler, 1995;Taylor et al, 1990;Weinberger et al, 1995). The current study was an attempt to apply the results of such trials to a 'real world' setting in order to evaluate its costs, applicability, acceptability (to both patients and physicians) and clinical effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Others have also demonstrated the superiority of a pharmacist interaction over other modes of intervention including computer‐generated feedback to physicians 12 . In an observational study, Shaffer and Wexler previously reported on the development of a referral lipid clinic team led by a clinical nurse, which included a clinical pharmacist, a nurse practitioner, dietitian, and clinical psychologist 13 . A consulting cardiologist reviewed all laboratory tests and therapeutic decisions at a weekly preclinic meeting.…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating the effectiveness of these specialty clinics have demonstrated significant improvements in lowering LDL-C levels, achieving lipid targets, and reducing other cardiac risk factors compared to usual care (Shaffer and Wexler 1995; Harris et al 1998; Wilson et al 1999; Yates et al 2001; Gavish et al 2002; Koren and Hunninghake 2004; Olson et al 2005). While the evidence clearly demonstrates that specialty cardiovascular risk reduction or lipid clinics are very effective in managing patients with dyslipidemias and other risks for CVD, all published evaluations of these practices have focused on the outcomes achieved while the patients are managed within the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have evaluated the effectiveness of these specialty clinics. Compared to management by primary care physicians or specialists in other nonlipid clinics, patients who are managed in CRRC or lipid clinics have lower LDL-C levels and are more likely to achieve their lipid targets (Shaffer and Wexler 1995; Harris et al 1998; Wilson et al 1999; Yates et al 2001; Gavish et al 2002; Koren and Hunninghake 2004; Olson et al 2005). Additional evidence demonstrates that patients referred to a CRRC were also able to achieve significant improvements in other cardiovascular (CV) risk factors, such as blood pressure and glycemic control (Olson et al 2005).…”
Section: Introductionmentioning
confidence: 99%